Community wellbeing and lived experiences during urban redevelopment in New Zealand: Te Hotonga Hapori – Connecting communities qualitative study protocol - Erica Hinckson; Vivienne Ivory; Julia McPhee; Megan Somerville Ryan; Moushumi Chaudhury; Lisa Mackay; Albert Refiti; Abby C. King; Tania Ka’ai; Scott Duncan (PLoS ONE, 2025)
Cities around the world are growing rapidly, and the demand for housing is subsequently increasing. Many governments have initiated large-scale redevelopment projects to address the problem but planning and implementation can significantly impact the wellbeing of residents. Evidence has shown that people-centred urban planning and redevelopment, including walkable areas, natural environments, and appealing public spaces, can enhance physical, mental, and social wellbeing. The impact of these designs on wellbeing is complex, and without community involvement, there is a risk that redevelopment may not meet the wellbeing needs of the residents. Community Wellbeing and Lived Experiences study is part of Te Hotonga Hapori – Connecting Communities research programme which aims to provide the evidence to improve liveability and wellbeing in neighbourhoods that are undergoing redevelopment. It seeks to empower communities by involving them directly in the redevelopment process. Guided by the culturally informed Te Hotonga Hapori Engagement Framework it comprises 5 components: i) Active relationship building; ii) Historical/cultural realities; iii) Community aspirations; iv) Building bridges; and v) Activation of neighbourhood urban and natural environments. Data collection will be undertaken using the Community Science Aotearoa process that is contextually specific to communities in New Zealand and adapted from the Our Voice Citizen Science Research method. Residents using Te Hotonga Hapori app will collect photos and narratives and share information about their lived experiences during the redevelopment using a six-step process of Engage, Discover, Discuss, Advocate, Change and Re-engage. Descriptive statistics will be produced in relation to the number and typology of photos and narratives collected. Qualitative thematic analysis will be used for narrative data obtained from downloaded app data, and community and group sessions. Braun and Clarke’s Thematic Analysis Framework will guide researchers through an iterative process and themes will be developed using the Attride-Stirling Thematic Networks Analytic Tool.